INFLUENCE OF SUBSTRATE TEMPERATURE ON THE STRUCTURAL AND OPTICAL PROPERTIES OF CdS THIN FILMS - Najiba Abdullah Hasan; Salah Qaduri Hazaa; Ameer Abdul Hussain Salih; Saba Jameel Hasan (Berkala Fisika Indonesia : Jurnal Ilmiah Fisika, Pembelajaran dan Aplikasinya, 2013)
CdS thin films were deposited on glass substrates at different temperatures by chemical spray pyrolysis. The prepared films were characterized by X-ray diffraction (XRD), Atomic Force Microscopy (AFM) and UV-Visible spectrophotometer. X-ray diffraction study shows a phase transition from cubic to hexagonal phase with the increase in substrate temperature from 200 °C to 400 °C and improves the crystalline of films. AFM analysis shows that the root mean square (RMS) surface roughness ranges from 15 nm for 200 °C films to 24.9 nm for 400 °C films. Optical characterization indicates that deposited film by chemical spray pyrolysis at different temperatures has a small decrease in band gap, which can be related to a phase change from cubic to hexagonal phase.